Analysis the relative light intensity using fiber optics sensor / Mohammad Latif Khairan - Khairan, Mohammad Latif (2014)
This paper is analysis the relative light intensity on the light sources such as infrare and visible to detect the gas bubbles and liquid (oil droplets) in water. The purpose of this project is to identify the existences of the gas bubbles and oil droplets which flow through the pipe.